Novel demineralized freeze-dried bovine bone xenograft nanoparticles (DFDBBX-NPs) for enhanced bone repair - Pratiwi, Ariyati Retno; Hussein, Mohd Zobir; Abdullah, Che Azurahanim Che; Istikharoh, Feni; Wardani, Sinta Candra; Fakurazi, Sharida; Abdelmonem, Mohamed (Wroclaw Medical University, 2026)
Background. The number of patients with bone defects is increasing. The treatment of damaged bones or bone defects is essential. Bone graft materials are frequently used in bone repair procedures. Researchers are attempting to replace damaged or defective bones with artificial ones, while also striving to improve the mechanical and biological compatibility of the scaffolds. Objectives. The study aimed to establish and validate novel demineralized freeze-dried bovine bone xenograft nanoparticles (DFDBBX-NPs) for enhancing bone repair. Material and methods. Demineralized freeze-dried bovine bone xenograft nanoparticles were extracted from bovine femoral bone. The physicochemical and biochemical properties of both native and demineralized freeze-dried materials were evaluated using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), and the Brunauer– Emmett–Teller (BET) analysis. Enzyme-linked immunosorbent assay (ELISA) kits were utilized to determine the content of type 1 collagen (Col-1) and bone morphogenetic protein-2 (BMP-2), water content percent-age (WCP), and enzymatic degradation. Results. The physicochemical analysis revealed non-porous DFDBBX-NPs with near spherical shapes of various sizes. The dried sample presented the nanoparticles agglomerated together, with an average size of 10–50 nm. The nanoparticles exhibit a type IV isotherm with an H3 hysteresis loop. They have a BET-specific surface area of 3 m2/g and a pore diameter of approx. 5.9 nm. The bioactive content of BMP-2 was higher than that of Col-1 in the DFDBBX-NPs. The DFDBBX-NP scaffold exhibited a slow rate of enzymatic degradation (0.098–0.240% over 14 days) and high water absorption (WCP ~202–215%). Conclusions. Demineralized freeze-dried bovine bone xenograft nanoparticles demonstrated remarkable potential for the development of new bone grafts.